The functions of self‐initiated self‐repair in the second language Chinese classroom1. (6th December 2012) - Simpson, Rebecca; Eisenchlas, Susana; Haugh, Michael
Abstract : Self‐repair analysis has often been used to gauge a learner's proficiency level, language acquisition or monitoring ability. This study questions these presumed links by examining the self‐initiated self‐repair practices of second language learners of Mandarin Chinese drawing from both classroom interaction data and stimulated recall interviews. While this link may not be as strong as previously suggested, self‐repair behaviour can reveal other information about the learner, including monitoring preferences, learning strategies, areas of difficulty, and perceptions about both their proficiency level and the target language. As such, self‐repair still appears to play an important role in the language learning process, albeit not the straightforward role that has often been assumed to date.